Emerging Dimensions of Women Rights for Inheritance in India: Exploring the Challenges and Implications of Women's Inheritance Rights in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Traditional Indian women may be taught from an early age that their husband's house is theirs,but this is not the case in law. In the 21st century, women's Inheritance rights are still far from genderequality, despite the fact that women were once forced to commit sati in order to avoid having to sharetheir husband's Inheritance with his family. In every marriage, there is an overt or hidden endeavour by thespouses to accumulate assets. These assets can be held alone by the husband or wife, or jointly by bothof them. An Indian family, the smallest unit in a society, has been affected by socio-culturaldevelopments in recent years. The growth of women's education has led to an increase in the number ofeducated women who use their skills outside the home in paid employment. Formerly reluctant to leavethe comfort of her own home, Indian women are now fighting for equal access to higher education andthe workforce. It is becoming increasingly clear that unless both husband and wife work, they cannot runa decent household. This is due to the economic stresses that families face, especially middle-classfamilies, which are in the majority. Demand for new consumer products in India is fueled in part bycommercials on television, which encourage women to work for money in order to elevate their socialstatus. However, currently it is a need rather than a choice for women to work for pay in order to raisethe family's standard of living. New legal issues have arisen as a result of this, such as how to divide upthe household's assets amongst the two couples' separate incomes, their joint contribution tohousehold expenses, and the purchase of real estate meant for joint use. Even though she was educatedand capable of earning, a housewife may find that she is unable to get any of the domestic assets thatshe had worked so hard to keep for her husband, who was out at work to generate money for the family.For a country with such a large population of divorced couples, it is regrettable that there is noestablished and specific rule for determining the respective Inheritance rights of the spouses when themarriage terminates by divorce.